2007
DOI: 10.1007/s00192-006-0293-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lower urinary tract symptoms among female elementary school teachers in Taipei

Abstract: The aim of this study was to estimate the prevalence of lower urinary tract symptoms (LUTS) among female elementary school teachers in Taipei. A total of 520 self-administered surveys were distributed to 26 elementary schools in Taipei City. Data analyses were based on 445 usable surveys. The prevalence rates for different types of LUTS ranged from 9.9 to 44.5%. The prevalence of urinary incontinence (UI; 26.7%) and nocturia (16.0%) fell within the prevalence estimates of these LUTS in North American and Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
(120 reference statements)
1
24
0
Order By: Relevance
“…17 The theoretical rationale and statistics for the sampling plan of the study reported here is more fully covered in a recent publication. 18 A systematic sampling method with probability proportional to size (pps) was used to select 26 elementary schools from all of the elementary schools in Taipei city. In each of the 26 selected elementary schools, a simple random sample of 20 teachers was used to achieve the required sample size of 502 teachers.…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…17 The theoretical rationale and statistics for the sampling plan of the study reported here is more fully covered in a recent publication. 18 A systematic sampling method with probability proportional to size (pps) was used to select 26 elementary schools from all of the elementary schools in Taipei city. In each of the 26 selected elementary schools, a simple random sample of 20 teachers was used to achieve the required sample size of 502 teachers.…”
Section: Samplementioning
confidence: 99%
“…In each of the 26 selected elementary schools, a simple random sample of 20 teachers was used to achieve the required sample size of 502 teachers. 18 The two-stage sampling method led to the same overall probability of selection for all teachers across all schools. This special type of sampling method, equal probability of selection method (epsem), guarantees that specific population elements have an equal selection probability.…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations